2008
DOI: 10.1002/elps.200800482
|View full text |Cite
|
Sign up to set email alerts
|

Continuous flow assay for the simultaneous measurement of the electrophoretic mobility, catalytic activity and its variation over time of individual molecules of Escherichia coli β‐galactosidase

Abstract: A CE-LIF detection-based assay was developed for the study of individual molecules of Escherichia coli beta-galactosidase. The assay allows for the simultaneous measurement of the electrophoretic mobility, catalytic activity and the variation in activity over time of individual enzyme molecules. In addition to showing the microheterogeneity of the enzyme molecules with respect to mobility and activity, it was demonstrated that at elevated temperatures the enzyme activity fluctuates over time. Incubation at var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 14 publications
3
36
0
Order By: Relevance
“…These enzymes are irreversibly denatured and contribute to the decrease in average activity over time. The denaturation temperature of β-galactosidase was calculated to be 55°C by CD experiments and confirmed by kinetic measurements (Figure S3A, B in File S1), and agrees well with denaturation temperatures reported in the literature [15], [24][26]. In the present experiments, denaturation of the enzymes was minimized by heating only to 47°C, which is below this denaturation temperature.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These enzymes are irreversibly denatured and contribute to the decrease in average activity over time. The denaturation temperature of β-galactosidase was calculated to be 55°C by CD experiments and confirmed by kinetic measurements (Figure S3A, B in File S1), and agrees well with denaturation temperatures reported in the literature [15], [24][26]. In the present experiments, denaturation of the enzymes was minimized by heating only to 47°C, which is below this denaturation temperature.…”
Section: Resultssupporting
confidence: 90%
“…Previous experiments indicate that enzymes can also exhibit long-lived activity differences at room temperature resulting in a distribution of activities between ostensibly identical molecules, termed “static heterogeneity” [2], [3], [12]. This static heterogeneity arises either from different conformations of the enzyme and/or different primary sequences between molecules, with the latter possibility resulting from errors in transcription and translation [11], [13][15]. When a nascent protein folds, it is possible that each molecule becomes trapped in a local energy minimum and many different local minima, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[99] Moreover, it was found that electrophoretic mobility and catalytic activity of individual molecules of β-galactosidase synthesized by E. coli were different, although they had potentiality to act on the same substrate molecule. [100]…”
Section: Characterization Of β-Galactosidasementioning
confidence: 99%
“…This observed heterogeneity is not limited to catalytic rate. Activation energy of catalysis (Craig et al 1996;Craig and Nichols 2008), K m (Craig et al 2010), V max (Craig et al 1996), electrophoretic mobility Craig and Nichols 2009), and dependence upon metal ions to maintain stability (Craig, Hall, and Goltz 2000) have also been found to vary amongst individual enzyme molecules. In addition, catalytic rate has been found to vary for a given enzyme molecule over time (Lu, Sun, and Xie 1998;Edman et al 1999;English et al 2006;Craig and Nichols 2008).…”
Section: Introductionmentioning
confidence: 96%